Learn Unity 4 for iOS Game Development - Chu, Philip; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
Unity is an incredibly powerful and popular game creation tool, and Unity 4 brings even more great features, including Mechanim animation. Learn Unity 4 for iOS Game Development will show you how to use Unity with Xcode to create fun, imaginative 3D games for iPhone, iPad, and iPod touch. You'll learn how to optimize your game for both speed and quality, how to test and profile your game, and how to get the most out of your iOS device features, including the gyroscope and accelerometer. You'll also learn how to incorporate the latest Game Center improvements in iOS 6 into your game, how to make sure your game gets into the App Store, and even how to promote your app and track revenue. If you have a great 3D game idea, and you want to make it a reality in the App Store, then Learn Unity 4 for iOS Game Development has exactly what you need.
Keywords: Computer science; Computer Science; Computer Science, general